Folktales and the Oral Tradition in the Grade 9 EFAL Classroom - Maluleke, Vukosi Linah; Smith, Cornelia; Makgatho (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Folktales stem from the oral tradition passed down over generations by the people who recounted them. These tales form part of the prescribed syllabus, CAPS, in South Africa specifically for Grade 9 English First Additional (EFAL) learners. The study explored the perceptions of folktales by 9 learners and 9 teachers. It was a qualitative study using purposeful sampling and an interpretivist research paradigm. The theoretical lens employed was Vygotsky’s constructivist theory. The study found that there are conflicting views on learning African folktales in English. The former Apartheid system’s impact has not completely been forgotten and there were still negative attitudes towards English as the language of the oppressor. Yet participants claimed that folktales needed to be revived and teachers must use narratives closer to their home and culture. Learners were positive towards learning folktales but there were those who deemed the stories as too simple to study in Grade 9. Teacher participants however revealed that learners benefit in that they learn new vocabulary and also about other cultures and life. Keywords: perception, English folktales, Grade 9 learners, South Africa 171 words